Literature Review : Pengaruh Citra Merek, Kualitas Produk, dan Inovasi Produk terhadap Minat Beli Konsumen - Kusuma, Shandy Saputra (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study presents a systematic analysis of various research results that discuss the impact of brand image, product quality, and innovation on consumer purchase intentions. The three variables are considered to play a strategic role in shaping consumer perceptions and behavioral tendencies, especially in the retail and consumer goods industry sectors. The approach used is a literature review from various academic sources, both scientific journals and other scientific works. The results show that all three consistently have a significant and positive influence on purchase intentions. Brand image forms a positive perception, product quality fosters trust, while innovation adds differentiation value to the products offered. This study emphasizes the importance of synergy between branding strategies, quality control, and product innovation to create purchasing interest from consumers.